Alpha-2-glycoprotein 1(AZGP1) regulates biological behaviors of LoVo cells by down-regulating mTOR signaling pathway and endogenous fatty acid synthesis. - Ligong Chang (Public Library of Science (PLoS), 2014)
AZGP1 is a multifaceted protein associated with lipid mobilization, a process that is regulated by FASN and other metabolic pathways such as mTOR signaling. The active mTOR signaling pathway has been found to be involved in a variety of tumors. However, it remains unclear whether it is involved in the regulation of AZGP1 and FASN. An AZGP1-expressing plasmid was transfected into a human colorectal cancer cell line (LoVo) with a low expression of AZGP1. The expression of AZGP1, FASN, eIF4E, p-mTOR, p-S6,and S6K1 were measured by Western blot analysis, and target genes were detected by RT-PCR. Cell proliferation was studied using the MTT and colony formation assays. The analysis of apoptosis and the cell cycle phase were assessed by flow cytometry. The capacity of cell migration was investigated using the transwell migration assay. We found that the expression of AZGP1 was up-regulated while the expression of FASN, eIF4E, p-mTOR, p-S6, and S6K1 were down-regulated in LoVo cells after AZGP1 was expressed. The proliferation of malignant cells was reduced in AZGP1-overexpression cells, which is consistent with an increased in the G2-arrest and apoptosis rate. Furthermore, the migration of AZGP1-overexpression cells was decreased. The overexpression of AZGP1 suppressed the activation of the mTOR pathway and endogenous FASN-regulated fatty acid synthesis, mitigating the malignant phenotype of LoVo cells. Herein, we provide evidence that AZGP1 may constitute a novel tumor suppressor for LoVo colorectal cancer cells.